A scoping review with bibliometric analysis of topic fluid in science education: State of the art and future directions - Misbah Misbah; Ida Hamidah; Siti Sriyati; Achmad Samsudin (Universitas PGRI Kanjuruhan Malang, 2024)
The aim of this scoping review is to provide an overview of scoping reviews in the literature on the topic of fluid science education through bibliometric analysis. The data search was carried out based on the Scopus database, then limitations were carried out based on certain criteria to obtain 146 documents. Publications on this topic have increased, especially in 2019-2023*. Then the author with the most citations was published in an international journal indexed by Scopus with quartile 1. Based on visualization using VOSviewer, 4 clusters were obtained and based on research in the last 2 years, both static and dynamic fluids are often associated with teachers, senior high schools, teaching, student learning, online learning. This research is the basis for further research related to the topic of fluids in science education. For example, fluid topics are rarely studied at the university level.